2015
DOI: 10.3109/15368378.2015.1048549
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields in medicine – the state of art

Abstract: In this work the authors introduced the procedure using the current knowledge relating to physical characteristic and biological effects of the magnetic fields. In the work the following methods were used: static magnetic fields, spatial magnetic fields, the variable magnetic fields both with laser therapy (magnetolaserotherapy) and variable magnetic fields both with light optical non-laser (magnetoledtherapy) talked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 8 publications
0
36
0
2
Order By: Relevance
“…6 In the mechanism of analgesic activity of alternating magnetic fields having low frequency, a substantial role is, among others, that of stimulation of release of endorphins and NO being a transmitter in nerve fibers, which transmit pain stimuli, anti-inflammatory, and antioedematic activities, as well as local improvement in blood supply to tissues in the ulceration area. [15][16][17]44,45 So far, the therapeutic efficacy of both presented methods in the treatment of leg ulcers of various origin has been observed in some published case histories. 4,[19][20][21]46 In the present study, we confirmed for first time that the application It should be emphasized that the time required for a single procedure and the number of procedures in the therapeutic cycle were similar for both analyzed therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 In the mechanism of analgesic activity of alternating magnetic fields having low frequency, a substantial role is, among others, that of stimulation of release of endorphins and NO being a transmitter in nerve fibers, which transmit pain stimuli, anti-inflammatory, and antioedematic activities, as well as local improvement in blood supply to tissues in the ulceration area. [15][16][17]44,45 So far, the therapeutic efficacy of both presented methods in the treatment of leg ulcers of various origin has been observed in some published case histories. 4,[19][20][21]46 In the present study, we confirmed for first time that the application It should be emphasized that the time required for a single procedure and the number of procedures in the therapeutic cycle were similar for both analyzed therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of synergistic therapeutic effect of variable magnetic fields and low‐energy light applied simultaneously by one device in the treatment of chronic wounds include, among others improvement of microcirculation in tissues and blood supply, intensification of oxygen utilization in soft tissues, stimulation of angiogenesis and vasodilatation, analgesic effect related to local inhibition of inflammation in the vicinity of ulceration, and stimulation of activity of endogenous opioid system, antiphlogistic and antiedematous effect related to local inhibition of inflammation in the vicinity of ulceration and stimulation of lymphatic drainage, activation of regeneration of epidermis regarding acceleration of nucleic acids replication, cell divisions, synthesis of proteins, and stimulation of fibroblasts resulting in increased synthesis of collagen, as well as bactericidal and fungicide effect 15‐17 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repetitive peripheral magnetic stimulation (rPMS) is a non-invasive, highly tolerable therapy based on relatively painless electromagnetic stimulation. It refers to the use of high-power electromagnetic waves that have the special ability to deeply penetrate neural structures and initiate therapeutic effects through still unelucidated pain modulatory mechanisms (4,5). Prior studies have reported therapeutic effects of rPMS on several types of musculoskeletal pain (6,7) or posttraumatic neuropathies due to spinal or axonal damage injury (8).…”
mentioning
confidence: 99%